2014
DOI: 10.1093/cid/ciu096
|View full text |Cite
|
Sign up to set email alerts
|

Birth Prevalence of Congenital Cytomegalovirus Among Infants of HIV-Infected Women on Prenatal Antiretroviral Prophylaxis in South Africa

Abstract: The birth prevalence of congenital CMV was high despite prenatal ARV prophylaxis, and was associated with advanced maternal immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 17 publications
7
44
2
4
Order By: Relevance
“…However, 5 recent studies shed some light on this question and met the criteria to be included in this review [12, 20, 2325]. The large French Perinatal Cohort Study showed lower rates of congenital CMV infection in HIV-exposed-uninfected infants in the cART era (1.2%), compared with the pre-cART era (3.5%), particularly if cART began in the first trimester ( P = .004); among HIV-infected infants, however, rates of congenital CMV infection remained high in the cART era [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 5 recent studies shed some light on this question and met the criteria to be included in this review [12, 20, 2325]. The large French Perinatal Cohort Study showed lower rates of congenital CMV infection in HIV-exposed-uninfected infants in the cART era (1.2%), compared with the pre-cART era (3.5%), particularly if cART began in the first trimester ( P = .004); among HIV-infected infants, however, rates of congenital CMV infection remained high in the cART era [24].…”
Section: Resultsmentioning
confidence: 99%
“…The study reported a congenital CMV infection rate of 2.9% (22 infants); no association of congenital CMV infection was observed with length or type of maternal antiretroviral prophylaxis. However, low maternal CD4 + T-cell count (<200 cells/μL) during pregnancy was associated with congenital CMV (adjusted OR, 2.9; 95% CI, 1.2–7.3) [25]. …”
Section: Resultsmentioning
confidence: 99%
“…Case and control mothers proved to be well matched on these characteristics, as determined by a 2-sided Fisher's exact test (Supplementary Table 1). Other variables that may independently influence the risk of cCMV transmission within this population of HIV-infected mothers, including plasma HIV RNA load and peripheral CD4 + T-cell count [17][18][19] Table 1). Maternal plasma CMV load was not controlled for in our study, as all of the CMV-transmitting women had undetectable CMV viremia by qPCR.…”
Section: Characteristics Of the Study Population And Selection Of Casmentioning
confidence: 99%
“…While the risk of cCMV transmission among HIV-infected women varies depending on the severity of HIV-induced immunosuppression, rates of transmission in studies conducted prior to widespread availability of antiretroviral therapy (ART) have been reported to be as high as 11% [13][14][15]. Importantly, maternal ART has been an extremely effective strategy for the reduction of in utero HIV transmission, yet the burden of cCMV infection in HIVexposed infants remains high in ART-recipient maternal populations (1.5%-3.5% transmission rate) [16][17][18][19][20][21]. Furthermore, HIV-exposed infants, regardless of their HIV transmission status, more frequently sustain symptomatic cCMV infection, compared with congenitally infected, HIV-unexposed infants [22].…”
mentioning
confidence: 99%
“…CMV infection in HIV-exposed infants was associated with decreased head circumference and delayed psychomotor development at 2 years of age [87]. Although cART during pregnancy decreases the risk of congenital and early postnatal CMV infection [88], higher incidence of congenital CMV is still reported in these infants and associated with microcephaly at birth [89,90]. Recently, a study from India described increased incidence of gastrointestinal infections in HIV-exposed infants compared with infants born to healthy women [84].…”
Section: Long-term Effects Of Fetal Exposure To Hiv On Infant Healthmentioning
confidence: 99%